Perbedaan Kemampuan Pemecahan Masalah Matematik Antar Siswa Yang Mendapatkan Pembelajaran Problem Based Learning (PBL) Dan Jigsaw: Penelitian Terhadap Mahasiswa Program Studi Matematika STKIP Garut Tahun Pelajaran 2012-2013 - Mubarok, Dede Miftahul; Nanang (Department of Mathematics Education Program IPI Garut, 2013)
The Purpose of research is to know the differences of ability problem-solving mathematics between students who get Problem Based learning (PBL) with Jigsaw and for now response students the model of learning who give. The results this research indicate: Not differences of ability problem solving mathematics between students who get Problem Based learning (PBL) learning with the students who get jigsaw learning. Response the students between experiment class 1 who get learning of model Problem Based learning (PBL) with the students who get learning of model jigsaw, Response the students show positive response although sometimes their students who show negative response.